An Extrusion System For Printing Hydrogel - Afandi, Nur Haziqah; Soon Chin Fhong, (Evolution in Electrical and Electronic Engineering, 2024)
This research delves into the transformative potential of extrusion-based bioprinting in tissue engineering and regenerative medicine. The study employs a system specifically designed for printing hydrogels, utilizing additive manufacturing principles to fabricate three-dimensional structures that closely resemble natural tissues. The process involves the layer-by-layer extrusion of bioinks, often hydrogel-based materials laden with cells, enabling the precise creation of complex biological constructs. The study's objectives encompass the design of a printing shape using Inkscape and its conversion to Gerber file format, the creation of an extrusion mechanism to be integrated with a current CNC machine for 3D bioprinter development, and the establishment of a bioprinting system capable of printing patterned biopolymers. The research successfully designed a geometric shape using Inkscape software, configured settings to display X, Y, and Z coordinates, and saved the file in G-code format for the printing system. An extrusion mechanism was created using a silicon tube, linking the controller to the extruder component and integrating it with an existing commercial CNC machine. The final objective involved the creation of a bioprinting system that can print patterned biopolymers, focusing on circular or cylindrical shapes to accurately replicate organ architecture. These geometric forms, first created in 2D, were piled using customized G-code to create 3D structures. The findings underscore the significant potential of extrusion-based bioprinting in advancing healthcare solutions.